2021
DOI: 10.1017/s0963180121000165
|View full text |Cite
|
Sign up to set email alerts
|

Limitations Using Neuroimaging to Reconstruct Mental State After a Crime

Abstract: Neuroimaging offers great potential to clinicians and researchers for a host of mental and physical conditions. The use of imaging has been trumpeted for forensic psychiatric and psychological evaluations to allow greater insight into the relationship between the brain and behavior. The results of imaging certainly can be used to inform clinical diagnoses; however, there continue to be limitations in using neuroimaging for insanity cases due to limited scientific backing for how neuroimaging can inform retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…However, the Court noted the low bar for admitting mitigating evidence in capital cases for sentencing purposes and indicated that excluding the defense expert's testimony based on the scans was a reversible error (Biddle & Chamberlain, 2013). Despite significant mitigating evidence, however, Lisa Montgomery was convicted and sentenced to death; her sentence was carried out on 13 January 2021 (Lynch et al., 2021; Vitacco et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Court noted the low bar for admitting mitigating evidence in capital cases for sentencing purposes and indicated that excluding the defense expert's testimony based on the scans was a reversible error (Biddle & Chamberlain, 2013). Despite significant mitigating evidence, however, Lisa Montgomery was convicted and sentenced to death; her sentence was carried out on 13 January 2021 (Lynch et al., 2021; Vitacco et al., 2021).…”
Section: Introductionmentioning
confidence: 99%